ASME/STLE 2007 International Joint Tribology Conference, Parts a and B 2007
DOI: 10.1115/ijtc2007-44215
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Behavior of Ultra-High Molecular Weight Polyethylene as a Function of Polymer Crystallinity

Abstract: In this study the friction and wear behavior of medical grade ultra-high molecular weight polyethylene (UHMWPE) (GUR 1050 resin) were evaluated as a function of polymer crystallinity. Crystallinity was controlled by heating UHMWPE samples to a temperature above its melting point and varying the hold time and cooling rates. Degree of crystallinity of the samples was evaluated using differential scanning calorimetry (DSC). Quantitative friction experiments were conducted at two different scales. A custom-made mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Wear behavior was also affected by the addition of DPPC into the tribological environment, Based on profilometer depth measurements, the HC‐PE sample showed higher wear resistance than LC‐PE in the control and DPPC‐lubricated reciprocating tests (Table II). The increased wear resistance of HC‐PE compared with LC‐PE in the control can be attributed to the increased hardness associated with increased crystallinity in UHMWPE 24. The presence of DPPC in the lubricant corresponded with decrease in wear depth only for the higher crystallinity sample.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Wear behavior was also affected by the addition of DPPC into the tribological environment, Based on profilometer depth measurements, the HC‐PE sample showed higher wear resistance than LC‐PE in the control and DPPC‐lubricated reciprocating tests (Table II). The increased wear resistance of HC‐PE compared with LC‐PE in the control can be attributed to the increased hardness associated with increased crystallinity in UHMWPE 24. The presence of DPPC in the lubricant corresponded with decrease in wear depth only for the higher crystallinity sample.…”
Section: Discussionmentioning
confidence: 94%
“…One potential for increasing adsorption of SAPL onto UHMWPE is to increase the crystallinity of the material. The authors have studies the effect of crystallinity on the friction and wear behavior of UHMWPE in dry conditions and found that increased crystallinity resulted in lower friction and wear 24…”
Section: Introductionmentioning
confidence: 99%
“…DSC analyses were performed using a Mettler Toledo DSC to determine the degree of crystallinity and melting temperature of the polymer composites before and after aging. This information is relevant as it holds information about the polymer structure, and it has been shown that the degree of crystallinity of polymers affect their mechanical properties and consequently their tribological performance [68].…”
Section: Dscmentioning
confidence: 99%
“…Semi-crystalline polymer mechanical properties depend on the crystallinity of the material, as they are dependent on how the polymer structure is distributed and the proportion of organized and random form. Moreover, the mechanical properties affect the tribological behavior, so the varying the crystallinity of a polymer may affect the tribological performance, which was identified by Karuppiah et al when studying the friction and wear of UHMWPE [68].…”
Section: Dscmentioning
confidence: 99%
“…The improving of wear resistance is related to cross-linking and reinforced materials that affecting the atomic or molecular arrangement, confirming a specific crystal structure [13]. Karuppiah et al discovered that the crystallinity effects on the wear resistance through increasing the crystallinity that decreases the friction force and the scratch depth [14]. Similar results were suggested by Wang and Ge [15].…”
Section: Introductionmentioning
confidence: 58%